2011
DOI: 10.1093/bmb/ldr047
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depression and its effects on child development: a review of evidence from low- and middle-income countries

Abstract: Nonetheless, there is a compelling case for the implementation of interventions to reduce the impact of PND on the quality of the mother-infant relationship and improve child outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
266
2
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(288 citation statements)
references
References 128 publications
8
266
2
12
Order By: Relevance
“…Antenatal and postnatal exposures independently affect child cognitive and emotional development 85,87 . In low-resource settings, the effects extend to childhood stunting and physical illness with antenatal depressive symptoms predicting higher rates of pre-term birth, failure to thrive in utero and low birth weight 88,89 . Animal studies of maternal antenatal stress have shown effects on various hormonal and chemical mediators (glucocorticoids, oxygen and glucose) that are associated with reduced fetal weight, gender-specific metabolic changes in the offspring and long-term adverse metabolic and renal effects 90,91 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Antenatal and postnatal exposures independently affect child cognitive and emotional development 85,87 . In low-resource settings, the effects extend to childhood stunting and physical illness with antenatal depressive symptoms predicting higher rates of pre-term birth, failure to thrive in utero and low birth weight 88,89 . Animal studies of maternal antenatal stress have shown effects on various hormonal and chemical mediators (glucocorticoids, oxygen and glucose) that are associated with reduced fetal weight, gender-specific metabolic changes in the offspring and long-term adverse metabolic and renal effects 90,91 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…Mat ernal depression across the postbirth period, a condition affecting approximately 15% of women in industrial societies, is a major public health concern. Not only is maternal depression among the most prevalent psychiatric disorders, but it also is the most underdiagnosed in the community and has direct negative consequences both for the suffering individual and for her child (1). Longitudinal studies have demonstrated that children of depressed mothers show greater vulnerability to psychopathology, particularly to anxiety and depressive disorders (2), oppositional conduct, neurocognitive deficits (3), and maladaptive social behavior (4).…”
Section: Discussionmentioning
confidence: 99%
“…1 Pregnancy in adolescents is considered a risk factor for symptoms of depression, considering that Vanessa Polina Pereira COSTA (a) Marcos Britto CORREA (b) Marília Leão GOETTEMS (b) Ricardo Tavares PINHEIRO (c) Flávio Fernando DEMARCO (b) pregnant adolescents present a higher prevalence of depressive symptoms than nonpregnant adolescents (16-44% vs 5-20%). 2 High levels of anxiety symptoms are also common during pregnancy 3 and in the first year postpartum.…”
Section: Introductionmentioning
confidence: 99%